Upper gastrointestinal bleed: a comparative outcomes study of pre and post implementation of management guidelines in the acute care surgery unit, Groote Schuur Hospital - Aborkis, Ismail (Department of Surgery, 2020)
Background: Upper gastrointestinal bleeding (UGIT) is a common presentation to hospital and can result in a significant morbidity, mortality and hospital costs. Consensus guidelines are present from various international expert bodies regarding the management of these patients and compliance with these guidelines is variable and is dependent on rigorous implementation and continuous audits. Aim: The primary aim of this study is to evaluate complaints to three aspects of management of UGITB (time of endoscopy ,use of dual endotherapy and haemoglubin trigger for transfusion) at Acute Care Surgery Unit, at Groote Schuur Hospital. Methods: This is a comparative study between a retrospective control group and a prospective cohort post implementation of a quality improvement program (QIP). Results: This study included 109 patients, 51 in the control and 58 in the QIP group. The two groups were statistically comparable in terms of demographics, clinical presentation, referral pattern and endoscopy finding. Over 80% in both groups had their endoscopy within 24 hours (Control 83.7%, QIP 81.6%). Time to endoscopy was not statistically significantly different between the Control and QIP groups for low and high-risk patients ((suspected varices or Modified Glasgow-Blatchford Score (MBS) >10)). However, when both groups are combined, patients with an MBS of >10 or more had a statistically shorter 'Time to scope’ by 8 hours than those with a score < 10 (p=0.02).